Property maintenance of TNB generation by TNB properties Sdn Bhd / Mohammad Fadli Ibrahih - Ibrahih, Mohammad Fadli; beeni Saaud, Ibeni Keffy I; Mohamad, Mohd Faizal; Adnan, Ahmad Azlan; Ali Hassan, Mohd Azhar; Asmuni, Norshahrina Hidayu; Sabtu, Azlina (2002)
Building Maintenance management is one of the important aspects in any property management. The understanding for a professional of building surveyor. Building maintenance caver not only the building facilities itself, as the need nowadays became more and more complex example changing on technology (technology movement and transferred). Design requirement organization management, financial, legal, and by law.